Holocaust : the Nazi persecution and murder of the Jews - Longerich, Peter 1955- (Oxford Univ. Press, 2010)
Focusing closely on the perpetrators and exploring the process of decision making, Longerich convincingly shows that anti-Semitism was not a mere by-product of the Nazis' political mobilization or an attempt to deflect the attention of the masses. Rather, from 1933 anti-Jewish policy was a central tenet of the Nazi movement's attempts to implement, disseminate, and secure National Socialist rule--and one which crucially shaped Nazi policy decisions--From publisher's description.